(untitled) (Al-Aasar, 2025)
War has always been a reality throughout human history, affecting not only the battlefield but also transforming the lives of thousands of people. Among the most sensitive and important human concerns during such conflicts are the individuals captured the prisoners of war (POWs). The questions of how they should be treated and what rights they possess have always tested the fundamental principles of ethics, religion, and law.Islamic Shariah is a complete code of life that upholds principles of humanity, justice, and mercy not only in times of peace but also during times of war. According to Islamic teachings, prisoners of war must be treated in a manner that does not violate their human dignity. Their food, shelter, medical care, clothing, and honor must be safeguarded this is a clear requirement of Shariah. The Seerah (life example) of the Prophet Muhammad ﷺ presents shining examples of high moral conduct and compassion even toward enemy captives. On the other hand, in the modern world, international laws particularly the Geneva Conventions provide a comprehensive framework for the protection and rights of prisoners of war. Under these laws, POWs are guaranteed protection from physical torture, psychological pressure, and inhumane treatment. They are entitled to religious freedom, medical facilities, adequate food, and communication rights.Both Islamic Shariah and international law emphasize that prisoners of war, being human beings, deserve honor and respect, and must be treated according to the principles of justice and humanity. However, the uniqueness of Islamic teachings lies in the fact that, in addition to legal requirements, they also incorporate moral excellence, compassion, and benevolence qualities that soothe human nature and bring hearts closer together.